The relative effect of job demands, resources, and personal resources on teaching quality and students’ engagement during the COVID-19 pandemic - Lep, Žan; Klemenčič Mirazchiyski, Eva; Mirazchiyski, Plamen V. (Frontiers in Psychology, 2023)
During the COVID-19 pandemic's school closures and the distance education that resulted from it, teachers were faced with an increasing workload and significant changes in their working environment. Because increased workload can result not only in worsened mental health and lower work motivation, but also in worsened learning outcomes, this article explores how teacher-perceived job demands, job resources, and personal resources are related to teachers' assessment of teaching quality and student engagement during the pandemic. Using the data of 1,422 8th grade teachers in Slovenia from the IEA Responses to Educational Disruptions Survey (REDS) survey, this study also explores the perceived level of support from different institutional actors and the utility of Job demands-resources model for this specific group of workers in a specific work setting. The results show that the teachers of 8th graders in Slovenia perceived a higher level of support from their closest working environment compared to the national bureaucracy. In terms of job demands, the increased workload in preparing the lessons had negative effect on both teaching quality and student engagement, while the reported increase in time spent on direct work with students and social support received (a job resource) contributed positively to both outcome variables. In line with theoretical expectations, personal resources were positive predictors of teaching quality and student engagement in our model. Compared with the initial expectations this study had based on the underlying theoretical model, the results paint a complex relationship between job characteristics and learning outcomes during distance learning. Thus, some of the challenges both teachers and policy-makers face and will continue to face in possible similar situations are discussed.